Actualization of the Reverence of Santri to the Kiai in Choosing a Life Partner in Pesantren - Abidin, Habibi Ali Zainal; Farid, Muhammad; Aliyah, Nelud Darajaatul; Syakur, Sultan Abdus (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Choosing a life partner is an important decision in a Muslim's life and must be made with consideration of Islamic teachings. In a pesantren environment, the relationship between santri and kiai plays a crucial role in this decision-making process, where the kiai serves not only as a teacher but also as a respected spiritual figure. This study aims to explore the influence of students’ devotion to their kiai in selecting a life partner at the Pesantren Habib Sholeh bin Alawi al-Haddad in Kubu Raya. The research employs a qualitative methodology using a case study approach, involving observations and in-depth interviews. The findings reveal that kiai emphasizes the importance of kafa’ah, or equality, in terms of religion, wealth, and behavior as criteria for choosing a life partner, with a strong emphasis on religious compatibility as the primary factor. Additionally, students demonstrate their devotion by following the kiai’s guidance, even when it may differ from their personal preferences. This research contributes to a better understanding of the dynamics of partner selection in pesantren contexts, highlighting the unique relationship between students and kiai as a foundation for family values.